Perspectives of patients with colorectal cancer liver metastases on e-consultation in transmural care: a qualitative study - T. Hellingman; M. L.H. van Beneden; C. M. den Bakker; B. M. Zonderhuis; G. Kazemier (BMC, 2023)
Abstract Background Comprehensive cancer networks have been established to deliver high-quality care for patients with cancer. Logistic challenges are faced, when patients need to be referred for specialized treatments. Despite strengthened privacy legislations, digital platforms are increasingly used to consult specialists from dedicated liver centers or refer patients with colorectal cancer liver metastases (CRLM) for local treatment strategies. This qualitative study aimed to explore the perspectives of patients with CRLM regarding e-consultation of transmural specialists. Methods A focus group study was conducted. Patients referred from regional hospitals to an academic liver center for treatment of CRLM were asked to participate. Focus group discussions were audio-recorded and transcribed verbatim. A thematic content analysis of data was conducted, comprising open, axial, and selective coding of the transcripts. The consolidated criteria for reporting qualitative research (COREQ) were used. Results Two focus groups were held, involving 11 patients and 8 relatives. Three major themes were identified with regard to e-consultation in transmural care: 'data management', 'expertise', and 'information and coordination'. Confidence in the expertise of physicians appeared most important during the course of treatment, as patients experienced uncertainty after diagnosis of cancer. Despite the privacy risks, use of digital communication platforms to contact experts in the field were strongly endorsed to improve eligibility for potentially curative treatment. Moreover, e-consultation of specialists may reduce waiting times, due to effective coordination of care. Conclusion Initiatives to improve medical data transfer between care providers were encouraged to achieve effective coordination of oncological care. The potential hazard of privacy violation associated with digital data exchange is accepted by patients and their relatives, provided that use of digital data improves patient's own health care, research or education.